The Values ​​of Islamic Education and Their Relevance in the Book "Seeking Knowledge of the Path to Heaven" by Yazid Bin Abdul Qadir Jawas: Nilai-Nilai Pendidikan Islam Dan Relevansinya Dalam Buku “Menuntut Ilmu Jalan Menuju Surga” Karya Yazid Bin Abdul Qadir Jawas - Alfi Rahma Aziz; Ainun Nadlif (Academia Open, 2022)
This article aims to add scientific references about the values ​​of Islamic education and their relevance in the book on the path to heaven by Yazid bin Abdul Qadir Jawas, so that later if anyone is looking for references on the values ​​of Islamic education and their relevance in books, studying the path to Paradise by Yazid bin Abdul Qadir Jawas can multiply so that it can make it easier for readers. The research approach used is library research, the data obtained from the literature with a theoretical and philosophical approach. The results of this study are the values ​​of Islamic education contained in the book by Yazid Bin Abdul Qadir Jawas. The value contained is the value of worship education, moral aqidah.